Assessing Work–Life Balance in Malta and Italy: A Cross-Cultural Investigation Using Exploratory Structural Equation Modelling (ESEM) - Bottaro R; De Giovanni K; Faraci P (Psychology Research and Behavior Management)
Rossella Bottaro,1,* Katya De Giovanni,2,* Palmira Faraci1,* 1Psychometric Laboratory, Department of Human and Social Sciences, University Kore of Enna, Enna, Italy; 2Department of Psychology, Faculty of Social Wellbeing – University of Malta, Msida, Malta*These authors contributed equally to this workCorrespondence: Rossella Bottaro, Department of Human and Social Sciences, University of Enna “Kore”, Cittadella Universitaria, Enna, 94100, Italy, Tel +39 0935 536536, Email rossella.bottaro1@gmail.com; rossella.bottaro@unikorestudent.itPurpose: Work-life balance (WLB) represents a well-established construct in several fields. However, the post-pandemic period has prompted substantial re-evaluations of the boundaries between professional and personal life among the general population, highlighting a critical need for renewed theoretical frameworks and empirical updates in this field. Our research focuses on the procedure of effectively assessing WLB in different cultural contexts, grounded in well-established theoretical foundations and involving the testing of measurement quality. Thus, the present cross-cultural study aimed to provide new evidence about the dimensionality, validity, reliability, and cultural invariance of the Work-Life Balance Scale and its practical impact on employee well-being.Participants and Methods: A sample of 362 employees (50% Maltese; 50% Italian), with a mean age of 43.36 (SD = 11.51) completed the WLBS in an online survey from March to April 2023. The cultural invariance was tested using the 13-model ESEM taxonomy of full measurement invariance. Moreover, through Network Analysis, the life satisfaction and optimism scales were administered to test the WLBS validity across countries.Results: Results showed ESEM model good fit (X2=127.609, df = 63, CFI = 0.963, TLI = 0.939, RMSEA = 0.053 [0.040– 0.066]) and less correlated latent factors than CFA. Tests of cultural invariance supported a weak invariance (ie, factor loadings and item uniqueness or factor variance/covariance matrix) across countries. Furthermore, the findings supported the validity and reliability of the scale.Conclusion: In conclusion, new evidence about the WLBS theoretical framework and dimensionality was provided by using the ESEM as a challenging psychometric approach. Results from this study also supported its psychometric features and the cross-cultural applicability of the WLBS in two different European countries. The practical recommendations for government policy were discussed.Keywords: exploratory structural equation modelling, work-life balance, cultural invariance